Taohong Siwu Decoction Regulates Cell Necrosis and Neuroinflammation in the Rat Middle Cerebral Artery Occlusion Model - Wang, Ni; Fei, Changyi; Chu, Furui; Huang, Shi; Pan, Lingyu; Peng, Daiyin; Duan, Xianchun (Frontiers in Pharmacology, 2021)
Cell necrosis and neuroinflammation play an important role in the brain injury induced by ischemic stroke. Previous studies reported that Taohong Siwu Decotion（THSWD）can reduce heart muscle cell necrosis and has anti-inflammatory properties. In this study, we investigated the effects of THSWD on cell necrosis and neuroinflammation in a rat model of middle cerebral artery occlusion (MCAO). Thirty-six male Sprague-Dawley(SD) rats were randomly divided into 3 groups with 12 rats in each group. They were sham operation group, MCAO model group and MCAO+THSWD group. We used ELISA to determine the levels of TNF-α, Mcp-1 and IL-1β inflammatory factors, and immunohistochemistry to detect the number of microglia and neutrophils in rat brain. qRT-PCR and Western blot were used to detect the mRNA and protein expression levels of IBA and MPO inflammatory factors and TNF-α/RIP1/RIP3/MLKL pathway in rat brain. and protein expression levels. Comparing with the sham operation group, the expression of MCP-1,IL-1β, IBA and MPO inflammatory factors and the TNF-α/RIP1/RIP3/MLKL pathway were significantly up-regulated in the MCAO group. Comparing with the MCAO group, the expressions of MCP-1,IL-1β, IBA, MPO inflammatory factors and TNF-α/RIP1/RIP3/MLKL pathway were significantly down-regulated in MCAO+THSWD group. THSWD can reduce the expression levels of MCP-1, IL-1β, IBA and MPO inflammatory factors as well as the TNF-α/RIP1/RIP3/MLKL pathway. Meanwhile, it can reduce the necrosis and inflammation of brain cells after cerebral ischemia, so as to protect the brain tissue of rats.